Synthesis, characterisation and reactivity studies of μ(α, ω)-alkanediyl complexes of ruthenium, iron and cobalt - Finch, Karol Paula (Department of Chemistry, 2016)
The new series of μ(α, ω)-alkanediyl compounds of ruthenium, [CpRu(CO)₂]₂[μ-(CH₂)ₙ], where n=5-10, have been prepared from Na[CpRu(CO)₂] and the corresponding diiodoalkane. These compounds, which are stable crystalline solids at ambient temperature, have been fully characterised by microanalysis, infrared, ¹H and ¹³C NMR spectroscopy, melting point and mass spectrometry. The new heterodinuclear complex [Cp(CO)₂Fe(CH₂)₄Ru(CO)₂Cp] has been synthesised by the reaction of [CpFe(CO)₂(CH₂)₄I] with Na[CpRu(CO)₂] and characterised by all the above mentioned techniques.